Characterization of macular choroid in normal‐tension glaucoma: a swept‐source optical coherence tomography study. Issue 8 (6th March 2021) - Wang, Yu Meng; Hui, Vivian W. K.; Shi, Jian; Wong, Mandy O. M.; Chan, Poemen P.; Chan, Noel; Lai, Isabel; Cheung, Carol Y.; Tham, Clement C.
Abstract: Purpose: To investigate the features of the small‐to‐medium (choriocapillaris and Sattler's layer) and large (Haller's layer) sized vessel layers of the macular choroid in normal‐tension glaucoma (NTG) patients using swept‐source optical coherence tomography (SS‐OCT). Methods: We conducted an observational cross‐sectional study in 234 NTG eyes from 134 patients, and 203 normal eyes from 109 non‐glaucomatous control subjects. We used Image J to segment the choroidal layer and then a Python script to measure the average macular choroidal thickness (MCT) and choroidal vascular index (CVI) of two vessel layers at five different locations. Quantitative optical coherence tomography angiography (OCTA) metrics for the superficial capillary plexus (SCP) and deep capillary plexus (DCP) at macular region were also measured by a customized MATLAB program. Generalized estimating equations (GEE) models were performed to determine ocular and demographic factors associated with the choroidal metrics, adjusting for inter‐eye correlation. Results: Significant average MCT thinning was found in NTG eyes at all five locations of the two layers, in comparison with controls (all p ≤ 0.05). In addition, compared with control eyes, significant decrease in CVI was found in NTG eyes at all five sections of the large sized vessel layer: 500 µm nasal and temporal to macula (p = 0.002), 1500 µm nasal (p < 0.001), 2500 µm nasal (p = 0.001), 1500 µm temporal (p < 0.001) and 2500 µm temporal (p = 0.004). In contrast, no significant CVI difference was detected in the small‐to‐medium sized vessel layer. In the comparison of OCTA metrics of SCP and DCP at macular region between NTG and normal eyes, there were no significant difference of parafoveal vessel density (VD), foveal avascular zone (FAZ) area, FAZ circularity and fractal dimension (FD) in both layers. Conclusion: We found significant alterations in macular choroidal vascularity (reduced CVI and thinner layer) in NTG patients. Such alterations are more pronounced in the Haller's layer, rather than the choriocapillaris & Sattler's layer, in NTG. Choroidal layer may be more related to vasculature changes at macular region in NTG.